PENGARUH PENJUALAN ADAPTIF DAN ORIENTASI SMART-WORKING TERHADAP KREATIVITAS STRATEGI PEMASARAN UNTUK MENINGKATKAN KINERJA BISNIS IBO DALAM MULTI LEVEL MARKETING PT ORIFLAME INDONESIA DI MEDAN - Martin Luter Purba (Universitas Medan Area, 2014)
The development of multi-level marketing company has been very much influenced by the performance of the Independent Business Owners (IBO) in forming the network to market their product. The problems settled in this study were adaptive selling, and smart-working orientation had direct influence on the performance of IBO business through marketing strategy creativity in multi-level marketing of PT ORIFLAME Indonesia in Medan. The purpose of this descriptive quantitative study was to find out and analyze adaptive selling, and smart-working orientation had direct influence on the performance of IBO business through marketing strategy creativity in multi-level marketing of PT ORIFLAME Indonesia in Medan by busing the theory of Marketing Management related to organizational committment, adaptive selling, smart-working orientation and working relationship satisfaction, marketing strategy creativity, and performance. The population of this study was 500 IBO of PT ORIFLAME Indonesia level 9% to 21% who were active in the working area of Medan from january to December 2014 and 100 of them were selected to be the samples for this study. The data for this study were obtained through interviews, questionnaire distribution, and documentation study. The data obtained were analyzed through Path Analysis consisting of direct and indirect influence analysis. The result of this study showed that Adaptive Selling, and Smart-Working Orientation had positive to influence Marketing Strategy Creativity, and Business Performance